Acute T cell‐mediated rejection accompanied by C4d‐negative acute antibody‐mediated rejection and cell debris in tubulus: A case report. (July 2015) - Takamura, Tsuyoshi; Yamamoto, Izumi; Nakada, Yasuyuki; Katsumata, Haruki; Yamakawa, Takafumi; Furuya, Maiko; Mafune, Aki; Kobayashi, Akimitsu; Tanno, Yudo; Miki, Jun; Ohkido, Ichiro; Tsuboi, Nobuo; et al.
Abstract: Herein, we report a complicated case of acute T‐cell‐mediated rejection (ACR) accompanied by C4d‐negative acute antibody‐mediated rejection (AMR) and cell debris in tubulus. A 32 year‐old male was admitted for an episode biopsy with a serum creatinine (S‐Cr) level of 1.83 mg/dL and pyuria (20–29 white blood cells per high power field) 49 days following kidney transplantation. Histological features included three distinct entities, mainly, in one of the three specimens: 1) focal aggressive tubulointerstitial inflammatory cell infiltration with moderate tubulitis, 2) inflammatory cell infiltration in peritubular capillaries (including neutrophils) and glomerular capillaries, and 3) cell debris consisting mainly of neutrophils in tubulus. Laboratory examination revealed evidence of non‐human leukocyte antigen donor‐specific antibodies. However, urinary culture and gram staining were negative. Considering both the histological and laboratory findings, the patient was diagnosed with ACR accompanied by C4d‐negative AMR and suspicion of a urinary tract infection (UTI). The patient was treated for three consecutive days with steroid pulse therapy. The patient's S‐Cr level decreased to ∼1.5 mg/dL following treatment and did not increase thereafter. A second biopsy 133 days following kidney transplantation showed an excellent response to treatment and revealed no evidence of rejection. This case report demonstrates the difficulty in the diagnosis of, and therapy for, the complicated pathological findings of ACR, AMR and suspicion of a UTI.